DNA Polymerase I-Dependent Mutants of Coliphage Lambda - Shizuya, Hiroaki (1974)
Mutagenized lysates of bacteriophage lambda were screened for mutants unable to plate on DNA polymerase I-deficient (polA(−)) hosts. The mutants obtained were all recombination deficient (red(−)). These mutants, like red(−) and gam(−) mutants previously isolated by others, grow more poorly than wild-type λ even on polA(+) hosts (burst size 14 to 30% of wild-type λ.) In a polA(−) host, the burst size of red(−) and gam(−) mutants is reduced an additional five- to tenfold, and lysis is delayed. Wild-type λ grows normally in polA(−) hosts. Neither λN(−)nin (which doesn't express red or gam) nor λbio phages (from which all or part of the red-gam region is deleted) form plaques on polA(−) hosts. Apparent revertants, able to plate on polA(−) hosts, have been selected from both λN(−)nin and λbio. Those derived from N(−)nin seem to be N(−)nin cro(−) mutants; whereas those coming from λ bio have a new bypass mutation (pas) that lies between genes P and Q.